Seorang penderita syok anafilaksis dengan allergic myocardial infarction (kounis syndrome) - I Putu Ary Wismayana; I Ketut Suardamana (DiscoverSys Inc., 2021)
Background: Kounis syndrome (KS) is defined as the concurrence of acute coronary syndromes associated with mast-cell and platelet activation in the setting of allergic or anaphylactic insults. Prevalence of KS is considered rare, estimated 1.1% of hospitalized allergic reaction patient, with mortality rate 7%. Case Report: Case of 39 years old male without history of coronary artery disease, having dyspnea, chest discomfort, and pruritus after eating skipjack tuna. 12 lead electrocardiogram showing ST depression segment on lead II, III, and aVF. Patient diagnose as Kounis syndrome variant type I. Treatment of Kounis Syndrome begins with cessation of the causative agent. After therapy using epinephrine and intravenous corticosteroid, clinical improvement was achieved, and ST segment depression on electrocardiogram resolved. Conclusion: Kounis syndrome is a rare disorder which need careful assessment and swift management. The diagnosis confirmed with sign and symptoms of allergic along with disorder in cardiovascular system. Latar Belakang: Kounis Syndrome (KS) didefinisikan sebagai sindrom koroner akut yang terjadi bersamaan dengan aktivasi sel mast dan trombosit dalam keadaan alergi atau anafilaksis. Prevalensi KS tergolong jarang, diperkirakan 1,1% dari pasien reaksi alergi yang dirawat di rumah sakit, dengan angka kematian 7%. Laporan Kasus: Laki-laki 39 tahun tanpa riwayat penyakit jantung koroner, sesak nafas, rasa tidak nyaman di dada, dan pruritus setelah makan ikan cakalang. Elektrokardiogram 12 sadapan menunjukkan segmen depresi ST pada sadapan II, III, dan aVF. Diagnosis pasien sebagai sindrom Kounis varian tipe I. Pengobatan Sindrom Kounis dimulai dengan penghentian agen penyebab. Setelah terapi menggunakan epinefrin dan kortikosteroid intravena, perbaikan klinis dicapai serta depresi segmen ST pada elektrokardiogram teratasi. Simpulan: Kounis syndrome adalah kelainan langka yang membutuhkan penilaian yang cermat dan penanganan yang cepat. Diagnosis ditegakkan dengan adanya tanda dan gejala alergi disertai gangguan pada sistem kardiovaskular.